SELECTION AND IMPLEMENTATION OF TASKS: AN ACCOUNT OF TEACHERS’ TASK PRACTICES - Sanni, Rasheed (Sokoto Educational Review, 2018)
The Study presented in this paper is part of a larger study, on task practices and teachers’ knowledge, towards the degree of Doctor of Philosophy. Key to the learning afforded by classroom mathematics is the tasks that were used during lessons. Since different tasks afford different learning opportunities, this paper was conceived to analyse tasks in terms of their qualities and what learning opportunities they ajford. The paper presents an analysis of tasks used in two classroom contexts in Lagos State. The findings show that 74% of the tasks are of low cognitive level, using Stein et a l’s framework; that about 50% of tasks were solved by the teacher in the guise of giving examples; and most importantly, even though the tasks are of low cognitive level, learners were operating at relational level of the SOLO taxonomy. However, since the aim is to get learners extended to the abstract level, the paper recommends that more tasks at the higher cognitive level need to be implemented in classroom.